Corrosion properties of TiNi medical alloy with bioinert coatings - Urban, V. I. (2023)
A comparative analysis of the barrier properties and corrosion resistance of bioinert coatings of tantalum, zirconium nitride, stainless steel of the 12X18H10T grade, as well as diamond-like coating (DLC) deposited on the surface of the medical alloy Ti–50.8 at % Ni (TiNi) has been performed. All the coatings are characterized by high barrier properties with respect to the yield of nickel in the biological medium for a long time, whereas, in the case of uncoated TiNi, the concentration of nickel in the test solution increases rapidly and exceeds the permissible amount of migration after 60 days of exposure. Electroplating TiNi–bioinertcoating pairs demonstrate a corrosive behavior determined by the nature of the coating material. The most resistant to galvanic corrosion is the TiNi –Ta pair, for which no signs of corrosion processes were detected on any of the elements of the pair after exposure in a model solution for 24 h. The pairs TiNi–12X18H10T and TiNi–DLC have shown the worst corrosion resistance among the studied pairs: extensive corrosion areas were observed on one of the elements of the pairs.